Confinement effects on decay rate of surface electron states over liquid helium: Электроны над жидким гелием - Sokolov, S.S.; Villas-Bôoas, J.M.; Monarkha, Yu.P.; Studart, Nelson (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The decay rate of excited states of surface electrons in liquid helium, trapped in a quantum dot system, is evaluated, taking into account the process of spontaneous radiation of two-ripplons with short wavelength. We find that the values of the decay rate in later process are rather higher than those for the one-ripplon process previously calculated. The upper-bound limit lifetime of excited states of surface electrons in a quantumdot is found to be t < 10-6–10-7 s.